How Effective Has Global Entrepreneurship Been As A Tool For Economic Growth? - Ike Egboga; Umaru Zubairu (Journal of Business and Behavioural Entrepreneurship, 2020)
The objective of this study was to conduct a critical review of entrepreneurship in a global / international context and to determine, based on empirical literature reviews whether it has been an effective tool for economic growth. The study adopted the Systematic Quantitative Assessment Technique (SQAT) in identifying and reviewing peer reviewed journal articles, conference papers and book chapters published between the period 2009-2019 which had empirically examined the link between entrepreneurship on a global basis and economic growth. The study was categorized into three (3) geographical groups based on national income levels – low income, medium income and high income countries which also correspond with their respective levels of economic development. Based on the evidence and review thereon conducted by this study, it was concluded that global entrepreneurship has been an effective tool for economic growth and that the degree of effectiveness increases with national income levels or degree of economic development.